2009
DOI: 10.1128/jcm.00264-09
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Thin Layer Agar Method for Diagnosis of Smear-Negative Pulmonary Tuberculosis in a Setting with a High Prevalence of Human Immunodeficiency Virus Infection in Homa Bay, Kenya

Abstract: The objective of this study was to evaluate the performance of a low-cost method, the thin layer agar (TLA) method, for the diagnosis of smear-negative patients. This prospective study was performed in Homa Bay District Hospital in Kenya. Out of 1,584 smear-negative sputum samples, 212 (13.5%) were positive by culture in Löwenstein-Jensen medium (LJ) and 220 (14%) were positive by the TLA method. The sensitivities of LJ and TLA were 71% and 74%, respectively. TLA could become an affordable method for the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…The performance of both cultures was lower in smear negative samples, in particular for LJ. This is in agreement with other studies and was reported also for genetic testing and liquid culture .…”
Section: Discussionsupporting
confidence: 94%
“…The performance of both cultures was lower in smear negative samples, in particular for LJ. This is in agreement with other studies and was reported also for genetic testing and liquid culture .…”
Section: Discussionsupporting
confidence: 94%
“…6 Robledo et al, in a multicenter study, found rates of between 2.7% and 9.5%. 16 These higher rates may be due to the lower concentration of antibiotics added to the medium (0.02 ll/ml instead of the 4.0 ll/ml used in our study).…”
Section: Discussionmentioning
confidence: 99%
“…5 When used for smear-positive samples, the median time required for mycobacterial detection is 14 days, vs. 9.6 days with the liquid culture BACTECe MGITe 960 system (BD, Sparks, MD, USA) and 23 days using solid Löwenstein-Jensen (LJ) medium. [6][7][8] However, TLA culture can yield high contamination rates when inoculated with samples previously treated with Petroff or NALC-NaOH alone. 6,7 The combined application of NALC-NaOH and CPC has rarely been described, and combination of CPC with the Petroff method is discouraged.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this system is costly, its consumables are not easily available, and it requires technical expertise. Parallel to the progress in automated systems, much work has also been published on the development of rapid but economical methods which are equally effective and comparable to automated systems, especially for resource-limited countries (1,11,12,15,18). Drancourt et al were the first to report the incidental growth of M. tuberculosis colonies on blood agar and termed this finding the "end of dogma" (7).…”
mentioning
confidence: 99%